Incidence, predictors and prognostic significance of thromboembolic disease in patients with advanced ALK-rearranged non-small cell lung cancer. Issue 5 (3rd May 2018) - Zugazagoitia, Jon; Biosca, Mercedes; Oliveira, Julio; Olmedo, María Eugenia; Dómine, Manuel; Nadal, Ernest; Ruffinelli, José Carlos; Muñoz, Nerea; Luna, Ana María; Hernández, Berta; Martínez, Maite; Gallego, Iria; et al.
Thromboembolic disease is fairly common in patients with lung cancer [1–3]. This incidence seems to be higher in patients with lung adenocarcinomas [4], with approximately 15% of those with advanced stage disease developing venous thromboembolisms (VTE) during the whole course of their disease [5–7]. Pulmonary adenocarcinomas are a heterogeneous group of diseases that can be stratified according to the presence of major oncogenic driver alterations. Anaplastic lymphoma kinase ( ALK ) rearrangements are detected in approximately 4% of these cases [8]. Isolated reports have suggested that patients bearing ALK -rearranged tumours might have a higher than expected incidence of thromboembolisms [9, 10]. In the present study, we have analysed the incidence, predictors and prognostic significance of thromboembolic events in a large, multi-institutional and homogeneous cohort of advanced stage patients with ALK -rearranged lung cancers from Spain and Portugal. Our primary objective was to estimate the incidence of thromboembolic events and their association with overall survival in these patients. High incidence and prognostic relevance of thromboembolic disease in patients with ALK-rearranged NSCLCs http://ow.ly/DEZr30j6kC8